2018
DOI: 10.3390/su10051402
|View full text |Cite
|
Sign up to set email alerts
|

Collection and Remanufacturing of Waste Products under Patent Protection and Government Regulation

Abstract: There is increasing academic and pragmatic interest in leveraging patent rights to invigorate remanufacturing for waste products under governmental interventions via regulations and reward-penalty instruments. In practice, many original manufacturers that are possessed with intellectual property rights allow third-party remanufacturers to implement reproducing operations through authorization and charging licensing fees. The general purpose of this paper is to explore favorable strategies for a closed-loop sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…Based on this study, Hong et al [20] investigated the optimal collection and remanufacturing decisions by considering competition not only in the forward channel but also in the reverse one. Further, Zhang et al [32] studied the same decisions but combing with government policy, and Huang and Wang [33] analyzed the effects of strategic consumer behavior on different remanufacturing scenarios. Considering different authorized members, Zhao et al [34] developed the operational decision models of OEMs and retailers with two cases, one of which the OEMs remanufacture and the other is to authorize remanufacturing to the retailers.…”
Section: Complexitymentioning
confidence: 99%
See 2 more Smart Citations
“…Based on this study, Hong et al [20] investigated the optimal collection and remanufacturing decisions by considering competition not only in the forward channel but also in the reverse one. Further, Zhang et al [32] studied the same decisions but combing with government policy, and Huang and Wang [33] analyzed the effects of strategic consumer behavior on different remanufacturing scenarios. Considering different authorized members, Zhao et al [34] developed the operational decision models of OEMs and retailers with two cases, one of which the OEMs remanufacture and the other is to authorize remanufacturing to the retailers.…”
Section: Complexitymentioning
confidence: 99%
“…By considering trade-ins for remanufactured products, Miao et al [41] derived the optimal pricing and production decisions under cap-and-trade regulations. Zhang et al [32,42] further introduced green innovation into a hybrid manufacturing and remanufacturing system and examined the joint pricing strategies and green innovation policy.…”
Section: Complexitymentioning
confidence: 99%
See 1 more Smart Citation
“…A mathematical model is developed considering the cost of implementation and the design of the proposed RFID based recovery channel. Reference [30] contributed on waste product collection and remanufacturing by taking the intellectual property rights of the original manufacturer into consideration. Reference [31] found that during the pretreatment process, the failure to operate on high-value materials caused significant economic losses (from 2006 to 2014, computer and mobile phone losses exceeded 70 million dollars).…”
Section: Innovation Input Incentives In Remanufacturing Closed-loop Supply Chainmentioning
confidence: 99%
“…Owing to technology innovation and mass industrial production, new products have burgeoned around the world, generating many waste products, and severely affecting the environment [ 1 , 2 , 3 , 4 , 5 ]. Confronting the situation, remanufacturing, which involves a series of processes that restore end-of-life products, parts or components, and returns them back to as-new conditions, has become a global strategy to deal with the massive amount of scrapped products [ 6 , 7 , 8 , 9 ]. The scrapped products processed by remanufacturing are referred as “Remanufactured Products” which can match the same properties and performance of the original ones [ 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%